Od linearnej do cyrkularnej komunikacji literackiej, a stąd do milczenia (O sytuacji we współczesnych doktrynach literackich) - Kuźma, Erazm (Wydawnictwo Naukowe UAM, 2002)
This paper is a part of a whole which will be published later in a book. The first section concerns ambiguities of contemporary terms: "communication", "literature", "literary communication". The second part is devoted to the turn from linearity to circularity in the philosophy of Jaspers and Heidegger. The third part - to the same turn in sociology of Habermas and Luhmann. The fourth part - not included here - examins the turn to circularity in hermeneutics, Marxism, structuralism and deconstruction. The last part contains the outlook on the future of literary theory and literary scholarship.
From the linear to the circular literary communication and from there to silence (On the situation in the modern literary doctrines)